Triazole + strobilurin controls cercosporiosis and coffee rust, and biostimulants + sucrose reduces phytotoxicity (Research, Society and Development, 2025)
Diseases such as cercospora, rust and problems with phytotoxicity are limitations in coffee production. The aim of this work was to reaffirm the efficiency of chemical control based on the chemical groups Triazol + Stribolurin on cercospora and coffee rust and its phytotoxic effect, as well as to verify whether biostimulants or 4% sucrose can minimize phytotoxicity. Two separate trials were carried out, the first of which included the following treatments: T1) Aproach® - 500 mL/ha, T2) Priori Xtra® - 750 mL/ha, T3) Sphere Max® - 400 mL/ha, T4) Opera® 1.5 L/ha, T5) Witness; the second trial included the following treatments: T1) Opera® 1.5 L/ha, T2) Opera® 1.5 L/ha + Fertiactyl® 0.5 L/ha, T3) Opera® 1.5 L + Stimulate® 1 L/ha, T4) Opera® 1.5 L/ha + Physio crop® 1. The first trial began in March 2022 on the Catuaí 62 Amarelo cultivar, with a hanging load of 20 bags/hectare, and the second in February 2023 on the Rubi MG 1185 cultivar, with no hanging load. The products based on triazole + strobilurin were efficient in controlling cercospora and rust, being similar to and superior to the control, the product based on picoxystrobin + cyproconazole, Aproach®, caused no reduction in plant growth, and the product based on pyraclostrobin + epoxiconazole, Opera®, caused the greatest reduction. The efficacy of the products Stimulate®, Fertiactyl® and sucrose 4% was also proven to mitigate the phytotoxic effects of the application of Opera®, improving the average number of leaves on the branches after treatment.